Rasio Prevalensi Anemia Ibu Bersalin Terhadap Kejadian Persalinan Preterm di RSUD Wonosari Tahun 2016 - Noviana Dewi Rengganis; Siti Tyastuti; Anita Rahmawati (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Preterm labor is a delivery that occurs in pregnancy before 37 weeks' gestation. Complications in preterm-born infants arethe single largest cause of neonatal death and are currently the leading cause of death among children under 5 years. InfantMortality Rate (IMR) in Indonesia is still very high at 34 of 1000 live births. The prevalence of preterm delivery in GunungkidulRegency in 2013 was 16.1%. Anemia is one of the causes of preterm labor. The incidence of anemia in Gunungkidul Regencyhas increased in the last 3 years. This study aims to determine the prevalence ratio of maternal anemia on the occurrence ofpreterm labor in Wonosari Hospital 2016. Type of observational analytical research with cross sectional design. The subjectof this research is maternity mother in RSUD Wonosari. Data collection was taken from secondary data that is maternityregister and medical record from January to December 2016. Target population in this study amounted to 953, with simplerandom sampling. The number of samples in this study amounted to 208 respondents. Data were analyzed using RatioPrevalensi (RP). Preterm birth mothers with anemia of 38,5% and preterm birth mothers who did not have anemia of 18.2%with analysis of RP = 2,115. The result indicates that maternal mother with anemia has a chance to experience preterm labor2.115 times bigger than mothers who are not anemia. (CI:1,330-3,365).